STUDIES ON HOST PREFERENCE OF PARASA LEPIDA ON SOME CULTIVARS OF HYBRID COCONUT IN SWAMPY AREA - Wily A. Baringbing; Bariyah Baringbing (International Coconut Community, 1994)
A two‑month f ield experiment to study host preference of the leaf‑eating caterpillar, Parasa lepida cramer, on 5 cultivars of hybrid coconut: Green Khina‑1, Brown Khina‑1, Nias Yellow Dwarf (NYD) x West African Tall (WAT),. Malayan Red Dwarf (MRD) x WAT, and Camerun Red Dwarf (CRD x Rennel Tall (RLT), aged 2.5 years, was carried out in swampy area of South Sumatra province, in 1991. A number of 30 palms, taken at random, from each block of the above mentioned hybrids were studied. Hence, there were 1SO trees observed altogether. The population of larvae per leaf as well as their dwellings in the fronds were recorded to investigate age of leaf consumed. Results of the study showed that none of the hybrids were resistant to P. lepida larvae. Cultivar of NYD x WAT was attacked more followed by Green Khina‑1, NYD x WAT, CRD x RLT, and Brown Khina ‑ 1. Leaves of half matures of all hybrids were preferred compared to those of the others.